Financial management in the sport industry / Matthew T. Brown, Daniel A. Rascher, Mark S. Nagel and Chad D. McEvoy. - Brown, Matthew T.; Rascher, Daniel A.; Nagel, Mark S.; McEvoy, Chad D., 1971- (Routledge, 2021)
Now in a fully revised and updated third edition, this essential textbook introduces the fundamentals of sport finance and sound financial management in the sport industry. It explains every aspect of finance from the perspective of the sport management practitioner, explaining key concepts and showing how to apply them in practice in the context of sport.